Entanglements and Weavings: Diffractive Approaches to Gender and Love - Byrne, Deirdre C.,; Schleicher, Marianne, (Value Inquiry Book Series ;, 2021)
This edited volume focuses on gender and love as phenomena that emerge through complex "entanglements and weavings". At a point where constructionist ideas are losing support, we interrogate theoretical paradigms to assess if constructionist notions still hold value or if new approaches are needed to address the effects of materiality and non-human agency on gender and love. Without claiming any unison or definite answers, we offer situated, agential cuts into Biblical and Rabbinic literature, ecosexual performance art, the writings of Ursula Le Guin and Angela Carter, butch identities, Bengali folktales, Ferzan Özpetek's cinema, Golem literature, sexual pursuits in Danish nightlife, mother-daughter relationships, women warriors in the PKK, and BDSM performances. Artistic photographer, Sara Davidmann, has contributed to the book with the cover illustration and a creative afterword including seven photographs on the effects of her photography studio on LGBTQ+ people.